Sailing and insight reproduction of Geo-Socio-Cultural unity of Nusantara/Indonesia Maritime: A study focus of Maritime Anthropology - Lampe, Munsi (ETNOSIA : Jurnal Etnografi Indonesia, 2021)
This paper aims to explain how Indonesia was conceptualized as the Indonesian Maritime Continent. From a geo-social perspective, maritime culture can be viewed in, three major dimensions. First, Indonesia is one of the largest archipelagic countries in the world with all the geographical potential, invaluable marine, and maritime resources; second, the potential for socio-cultural, socio-demographic, socio-economic, and long maritime cultural history within the framework of the unity of the Republic of Indonesia; and third, the existence of academic core and the maritime vision of Unhas, the idea of the Indonesian Maritime Continental Development which was launched by the government in 1995/1996, and the vision of maritime national development by President Joko Widodo marked the role of academics and governments in the dynamic process of development to the phase of maritime civilization in the future. In the context of developing maritime ethnographic studies and anthropological contributions to the development of maritime civilization in the future, ideas and academic commitment are needed to make the Indonesian Archipelagic State a large and unique area of maritime socio-cultural research development in the world and Southeast Asia in particular. Thus, interdisciplinary, transdisciplinary, comparative, and multidisciplinary research is needed to carry out broadly and intensively. For this reason, through my inauguration speech for Professor of Anthropology in Hasanuddin University, I introduced a focus of maritime anthropology studies on sailing experiences and the reproduction of Nusantara/Indonesian maritime geo-socio-cultural insights. Through the application of the concept of experience and reproduction of maritime geo-socio-cultural insights which were developed from the concept of maritime ethos disposition theory of reproduction from A.H.J. Prins as a mode of description and analysis, I found the categories of maritime cultural insights and attitudes of Indonesian sailors. They understand most of the territorial waters of the Nusantara (archipelago) and the resources within as common property, a space for interaction between groups of sailors who are diverse in their maritime ethnicity and culture, which in turn strengthens awareness and recognition of the unity of the homeland, culture, and nation that is Bhinneka Tunggal Ika (unity in diversity).